Wrestlers' perceptions of the professional skills of their coaches - Acak, M. (International Journal of Wrestling Science, 2014)
Purpose of this research is to determine the patterns of wrestlers in their perceptions of the professional skills of their coaches, as well as identify their positive and negative behaviors. The subjects of the study consisted of 69 voluntary athletes between the ages 16 and 34, who were active wrestlers from various provinces in Turkey. Data was collected through face-to-face interviews. Results of this research reveal that the less experienced athletes evaluate their coaches more positively. Statistically significant differences were found in their perceptions of technical development, competition and social sub-dimensions of their coaches according to the experience of the wrestlers. More negative evaluations were also observed in the technical and competition dimensions as years of experience increases. It was determined that students receiving education in a university evaluates their coaches more negatively. Athletes participating in the study stated that they were pleased with their coaches in many ways. However, it was determined that coaches often lack a long-term written program of special preparation in order to develop correct technique; and that coaches are not always proficient in analyzing the opposing competitors.